2019
DOI: 10.1073/pnas.1902747116
|View full text |Cite
|
Sign up to set email alerts
|

Maizesugary enhancer1(se1) is a gene affecting endosperm starch metabolism

Abstract: sugary enhancer1 (se1) is a naturally occurring mutant allele involved in starch metabolism in maize endosperm. It is a recessive modifier of sugary1 (su1) and commercially important in modern sweet corn breeding, but its molecular identity and mode of action remain unknown. Here, we developed a pair of near-isogenic lines, W822Gse (su1-ref/su1-ref se1/se1) and W822GSe (su1-ref/su1-ref Se1/Se1), that Mendelize the se1 phenotype in an su1-ref background. W822Gse kernels have lower starch and higher water solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 49 publications
1
24
0
4
Order By: Relevance
“…The STRUCTURE cluster that contained the majority of sweet corn lines is represented with high membership probability (>0.99) by the variety Golden Bantam and inbred line P39, two important genotypes in the history of sweet corn breeding. A second large STRUCTURE cluster traces back with high membership probability to IL677a, a su1 line which is also the source of the mutant gene sugary enhancer ( se ) 34 , a third mutant gene used in sweet corn breeding programs and recently cloned 35 . A DAPC calculated using only the sweet corn genotypes supported a cluster containing IL677a and further identified groups that contained additional lines known to have contributed to modern sweet corn breeding, such as Stowell’s Evergreen and Ia5125 4 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The STRUCTURE cluster that contained the majority of sweet corn lines is represented with high membership probability (>0.99) by the variety Golden Bantam and inbred line P39, two important genotypes in the history of sweet corn breeding. A second large STRUCTURE cluster traces back with high membership probability to IL677a, a su1 line which is also the source of the mutant gene sugary enhancer ( se ) 34 , a third mutant gene used in sweet corn breeding programs and recently cloned 35 . A DAPC calculated using only the sweet corn genotypes supported a cluster containing IL677a and further identified groups that contained additional lines known to have contributed to modern sweet corn breeding, such as Stowell’s Evergreen and Ia5125 4 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that the starch content in lotus seed still needs to be improved, with some main cultivars having their content lower than the average level of 47.12%, such as 'Taikong 3' (40.00%) and 'Jingguang 1' (42.66%). Previous studies have shown that understanding the mechanism of starch biosynthesis can successfully provide the molecular basis for breeding new varieties with high-starch content in crops, such as rice, corn and wheat [37][38][39][40]. Although the research on the mechanism of starch biosynthesis in lotus seed has attracted the attention of plant breeders, little is still known on the topic [2,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Most sugar analysis requires grinding tissue and measuring overall sugar levels, which precludes the cellular-level resolution required to detect spatial differences in sugar accumulation in a developing tissue. Starch, the major storage carbohydrate in plants, however, can be easily visualized by iodine staining (Zhang et al, 2019). In the inflorescence, starch accumulates at the base of developing spikelet meristems, but not in the spikelet meristem itself (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%